2007
DOI: 10.1016/j.ultrasmedbio.2006.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Thin Compression Paddles for Mammographically Compatible Ultrasound

Abstract: We are developing a combined digital mammography/3D ultrasound system to improve detection and/or characterization of breast lesions. Ultrasound scanning through a mammographic paddle could significantly reduce signal level, degrade beam focusing, and create reverberations. Thus, appropriate paddle choice is essential for accurate sonographic lesion detection and assessment with this system. In this study, we characterized ultrasound image quality through paddles of varying materials (lexan, polyurethane, TPX,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 20 publications
1
24
0
1
Order By: Relevance
“…An initial study (151) combined FFDM with three-dimensional automated breast US enabling coregistered dual-modality imaging and was subsequently modified for DBT with automated breast US. Development of a compression paddle compatible for both x-ray and US imaging (152), selection of US coupling media, and breast coverage with US particularly at the breast periphery that is not in contact with the compression paddle have been reported (153). In an analysis of 51 patients with masses (13 malignancies), Padilla et al (154) reported similar AUCs for DBT alone and the combined DBT and automated breast US, and an improvement in discriminating masses from simple cysts.…”
Section: Multimodality Imagingmentioning
confidence: 97%
“…An initial study (151) combined FFDM with three-dimensional automated breast US enabling coregistered dual-modality imaging and was subsequently modified for DBT with automated breast US. Development of a compression paddle compatible for both x-ray and US imaging (152), selection of US coupling media, and breast coverage with US particularly at the breast periphery that is not in contact with the compression paddle have been reported (153). In an analysis of 51 patients with masses (13 malignancies), Padilla et al (154) reported similar AUCs for DBT alone and the combined DBT and automated breast US, and an improvement in discriminating masses from simple cysts.…”
Section: Multimodality Imagingmentioning
confidence: 97%
“…Automated elasticity imaging (Booi 2007, Booi, et al 2007) and local compression by the scanning transducer (Carson, et al 2010) also are possible with this type of system. Quasi-static elasticity studies were performed earlier (Booi 2007, Booi, et al 2007) with solid, rather than mesh paddles.…”
Section: Discussionmentioning
confidence: 99%
“…Quasi-static elasticity studies were performed earlier (Booi 2007, Booi, et al 2007) with solid, rather than mesh paddles. Compression of the entire breast by the paddles, to stabilize the breast position, provided preloading of all the tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the breast, a multi modal breast phantom (Cirs inc. model 051 phantom) containing dense masses of 2 to 8 mm diameter and cystic lesions of 3 to 10 mm diameter is used. It is compressed between a 25 mm thick PVC plate (at the bottom) and a 6 mm thick PMP plate (at the top), both well suited regarding their low x-ray attenuation, PMP being equally well suited to let pass US [4]. Figure 6 show typical US-image of a lesion obtained with this set-up.…”
Section: Proposed Approachmentioning
confidence: 99%